(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
Five Simple, accurate and rapid spectrophotometric and conductometric methods were developed for the determination of four third generation cephalosporins, namely, cefotaxime sodium (I) , cefoperazone sodium (II), ceftazidime pentahydrate (III) and cefdinir (IV) in pure active ingredient, pharmaceutical dosage forms and human urine. Method A: is based on the reaction of the sulphide ions produced from the alkaline hydrolysis of the cited four drugs with P- aminophenol (PAP). This reaction results in a thionine dye (phenothiazine derivative) formation which exhibits maximum absorbance at 545 nm. Method B: is based on oxidation of drug (I and III) with a known excess of n-bromosuccinimide (NBS) in acidic medium followed by the determination of unreacted amount of n-bromosuccinimideÂ with metol and sulphanilic acid. The purple-red reaction product exhibits maximum absorbance at 520 nm. Method C: is based on the formation of yellow chelate between drug (IV) and palladium (II) chloride in buffered medium (pHÂ 3.5) with an absorption maximum at 314 nm.Â Method D: is based on the reaction of drug (IV) with aqueous ninhydrin to give yellow colored product in the presence of bicarbonate with an absorption maximum at 433 nm . Method E: A conductometric method is based on the reaction of the four cited drugs with phosphotungstic acid (PTA) forming an ion associate in aqueous medium. Validation of the proposed methods was carried out. All proposed methods were successfully applied for the commercial dosage forms of the cited drugs. Method C was successfully applied for the determination of cefdinir in human urine.